Code-switching in students’ group discussions in EFL classroom at a university level - Gendroyono, Gendroyono; Baharun, Hazleena (Universitas Ahmad Dahlan, 2023)
Code-switching is an activity when a person switches their language in a speech. Some research have been conducted in the field of code switching, however, very little was done in looking both the types and the reasons of doing it in the group discussion context. This research focuses on exploring the types of code-switching used by the students in EFL classroom during group discussion and the reasons why the students used code-switching during group discussion in EFL classroom. The methodology used in this research was a descriptive qualitative. There were three participants in this research, two females and one male aged 21 to 24-year-old which was done in a private university of Yogyakarta. In collecting the data, the researcher used interview and follow-up questions. And the finding of this research found that there were three types of code-switching used by the EFL student, the first one is tag switching, inter-sentential switching, and the last one is intra-sentential switching. Furthermore there were three reasons why the participants used code-switching. The first one is feeling comfortable in using their mother tongue, lacking the target language proficiency, and the last one is holding the floor.